Fuel drop impact on heated solid surface in film evaporation regime. (20th July 2019) - Bhat, Maanasa; Sakthikumar, R.; Sivakumar, D.
Highlights: Fuel drop impact on hot stainless steel surface using four different fuels presented. Temporal variation of drop diameter is deduced from high speed videos of drop impact. Fuel viscosity affects the trend of maximum spreading diameter with surface temperature. Formula for maximum diameter on heated surface in terms of surface temperature given. Abstract: This study reports an experimental investigation on the dynamics of impacting hydrocarbon fuel drops on a heated stainless steel surface in the film evaporation regime. The analysis is focused on the description of maximum spreading diameter of the impacting fuel drops on the heated surface kept at different temperatures below the boiling point of the fuel. By considering four different fuels of varying physical properties and fuel drops with impact velocity in the range 0.6 – 3.5 m/sec, the study explores a wide range of Weber number (30 – 902), Reynolds number (372 – 13457) and Ohnesorge number (0.0022 – 0.0151). The drop morphology and spreading dynamics on the heated surface are quantified by studying high speed videos of drop impact captured during experiments. Data analysis suggests that, in addition to Weber number and surface temperature, dynamic viscosity of the fuel also plays a role in determining the quantified trends of maximum spreading diameter. Existing theoretical models for the prediction of maximum diameter on unheated flat surfaces can be extended for drop impact on heated surfaces in the film evaporation regime by using surface temperature dependent fuel viscosity. With the support of the present experimental data, an empirical model involving an explicit surface temperature term is proposed for the prediction of maximum diameter on a heated surface in the film evaporation regime.